Phylogenetic reassessment of Specklinia and its allied genera in the Pleurothallidinae (Orchidaceae) - Karremans, Adam P.; Albertazzi, Federico J.; Bakker, Freek T.; Bogarín, Diego; Eurlings, Marcel C.m.; Pridgeon, Alec; Pupulin, Franco; Gravendeel, Barbara (Phytotaxa, 2016)
The phylogenetic relationships within Specklinia (Pleurothallidinae; Orchidaceae) and related genera are re-evaluated using Bayesian analyses of nrITS and chloroplast matK sequence data of a wide sampling of species. Specklinia is found paraphyletic in the DNA based trees, with species alternatively assigned to Muscarella proven distinct, monophyletic and easily recognizable. Specklinia as such includes about 100 morphologically highly diverse species. Their phenotypic differences have prompted the creation of up to eleven generic names within this relatively small group. Here we show not only that these morphologically divergent species are closely related, but also that they can still be recognized by certain conserved morphological traits. The genera Acostaea, Areldia, Empusella, Cucumeria, Gerardoa, Pseudoctomeria, Sarcinula, Sylphia, Tribulago and Tridelta are found embedded within Specklinia, and therefore reduced under the synonymy of the latter. Specklinia is confirmed as sister to a clade that includes Platystele, Scaphosepalum and Teagueia. Five well-supported subgenera are proposed for Specklinia and are characterized both geographically and morphologically. The species belonging to each subgenus are listed. Incaea is synonymized with Dryadella, while Rubellia is reduced under Platystele. New combinations for several species are proposed. The criteria for the generic delimitation of Specklinia and other genera in the Pleurothallidinae are discussed.